Rib cartilage, the panacea for post traumatic mid face deformity - Munjal, Manish; Munjal, Shubham; Nahar, Amandeep; Sharma, Salony; Chawla, Deeksha; Kaur, Hardeep; Sandhu, Loveleen; Gill, Ruchika; Chahal, Jasmeen; Rishi, Ojassivi; Joshi, Tanvi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Reconstitution of the facial profile can be achieved in a depressed‘midface “, by supplementation of the nasal osteo-cartilagious skeleton utilizing autologous tissue or synthetic prosthesis, Bone from the iliac crest and cartilages from the septum, cymba conchal and the rib are the accepted grafts in wide use. The costo-chondral junctional cartilage is ideal in situations demanding excess of graft, then can be harvested from the ear or the septum. Moreover, this graft though easily cut and mouldable, gives a rigid sharp profile to the nose. Utilization of the rib cartilage in a young gentleman with a post traumatic midrace deformity is being described.